Compliance Analysis of Land and Building Tax in The Regency of Bengkalis - Basri , Yesi Mutia; Nasir, Azwir; Julita (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to determine factors influence compliance of land and building Tax rural and urban areas (PBB-P2) in Bengkalis Regency This research uses mixed research method (Mix research) by using explanatory sequential method that is collecting qualitative data to help explain or elaborate on quantitative results. Knowledge, social norms, moral norms, tax sanctions, tax audits and tax socialization were analyzed as factors influencing PBB-P2 compliance. The population in this study was the United Nations Taxpayer PBB-P2 who was chosen by purposive sampling technique. A total of 256 respondents participated in this study. The results of data analysis using multiple regression shows social norms and tax sanctions that affect tax compliance of PBB-P2. The results of data analysis using multiple regression shows social norms, tax sanctions and tax audit that significant affect to tax compliance of land and building tax (PBB-P2) but tax knowladge not significant. The results of qualitative analysis through interviews and observations indicate that the efforts made by the government to increase tax compliance must be supported by justice and public trust in the government.